Neutral competition of stem cells is skewed by proliferative changes downstream of Hh and Hpo. (4th August 2014) - Amoyel, Marc; Simons, Benjamin D; Bach, Erika A
Abstract Neutral competition, an emerging feature of stem cell homeostasis, posits that individual stem cells can be lost and replaced by their neighbors stochastically, resulting in chance dominance of a clone at the niche. A single stem cell with an oncogenic mutation could bias this process and clonally spread the mutation throughout the stem cell pool. The Drosophila testis provides an ideal system for testing this model. The niche supports two stem cell populations that compete for niche occupancy. Here, we show that cyst stem cells (CySCs) conform to the paradigm of neutral competition and that clonal deregulation of either the Hedgehog (Hh) or Hippo (Hpo) pathway allows a single CySC to colonize the niche. We find that the driving force behind such behavior is accelerated proliferation. Our results demonstrate that a single stem cell colonizes its niche through oncogenic mutation by co‐opting an underlying homeostatic process.